Impact of Land Use Pattern on Rangeland Vegetation in Blue Nile State, Sudan (University of Khartoum Journal of Agricultural Sciences, 2022)
The study was conducted in‘Elrosieris’area, Blue Nile State, Sudan, at the end of autumn season on Novermber, 2018 to investigate the impact of land use type on natural rangelands vegetation. Two sites were selected; namely rangelands and abandoned croplands. Three transects of 100 m length were placed randomly in each of these sites. Species composition,plants cover and ground cover were determined using Parker loop method along these transects. Plant density (Plant/m2), frequency, biomass productivity (ton/ha) and carrying capacity, Tropical Livestock Unit (TLU/ha/yr) were determined using quadrate method applied along these transects. The data were analyzed using descriptive statistic and T- test. Theresults revealed that plant cover was higher in rangeland (87%) compared to abandoned cropland (79%). Bare soil was lower in rangeland (4%) than in abandoned cropland (8%). Pennisetum ramsum was dominant species inrangeland (70.67%) and less so in abandoned cropland (25.33%). Plant density was higher in rangeland (34.67 plant/m2) compared to abandoned cropland (11.58 plant/m2). The difference in productivity and carryingcapacity were very slight. The study concluded that Pennisetum ramsum was dominant in terms of cover and composition regardless of land use type. Plant density was better in rangeland. The differences in yield and carryingcapacity were close regarding land use pattern.
Keywords: Land use; pattern; abandoned cropland; carrying capacity